Species range contractions in geographic and environmental space - Ben C. Scheele; Geoffrey W. Heard; Simon Clulow; Jane A. Catford; Richard P. Duncan (Trends in Ecology & Evolution, 2026)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Modeling genetic benefits and financial costs of integrating biobanking into the conservation breeding of managed marsupials - Lachlan G. Howell; Peter R. Mawson; Pierre Comizzoli; Ryan R. Witt; Richard Frankham; Simon Clulow; Justine K. O'Brien; John Clulow; Paul Marinari; John C. Rodger (Conservation Biology, 2023)
Managed breeding programs are an important tool in marsupial conservation efforts but may be costly and have adverse genetic effects in unavoidably small captive colonies. Biobanking and assisted reproductive technologies (ARTs) could help overcome these challenges, but further demonstration of their potential is required to improve uptake. We used genetic and economic models to examine whether supplementing hypothetical captive populations of dibblers ( Parantechinus apicalis ) and numbats ( Myrmecobius fasciatus ) with biobanked founder sperm through ARTs could reduce inbreeding, lower required colony sizes, and reduce program costs. We also asked practitioners of the black‐footed ferret ( Mustela nigripes ) captive recovery program to complete a questionnaire to examine the resources and model species research pathways required to develop an optimized biobanking protocol in the black‐footed ferret. We used data from this questionnaire to devise similar costed research pathways for Australian marsupials. With biobanking and assisted reproduction, inbreeding was reduced on average by between 80% and 98%, colony sizes were on average 99% smaller, and program costs were 69‐ to 83‐fold lower. Integrating biobanking made long‐standing captive genetic retention targets possible in marsupials (90% source population heterozygosity for a minimum of 100 years) within realistic cost frameworks. Lessons from the use of biobanking technology that contributed to the recovery of the black‐footed ferret include the importance of adequate research funding (US$4.2 million), extensive partnerships that provide access to facilities and equipment, colony animals, appropriate research model species, and professional and technical staff required to address knowledge gaps to deliver an optimized biobanking protocol. Applied research investment of A$133 million across marsupial research pathways could deliver biobanking protocols for 15 of Australia's most at‐risk marsupial species and 7 model species. The technical expertise and ex situ facilities exist to emulate the success of the black‐footed ferret recovery program in threatened marsupials using these research pathways. All that is needed now for significant and cost‐effective conservation gains is greater investment by policy makers in marsupial ARTs.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Sustained absorption of delamanid from lipid-based formulations as a path to reduced frequency of administration - Gisela Ramirez; Anna C. Pham; Andrew J. Clulow; Malinda Salim; Adrian Hawley; Ben J. Boyd (Drug Delivery and Translational Research, 2021)
Delamanid is a poorly water-soluble drug currently being used for the treatment of tuberculosis. The high frequency of dosing leads to poor adherence for patients who live in lower economic and nomadic populations. Non-digestible self-assembling lipids as a formulation approach for poorly water-soluble drugs have previously been shown to extend the window of absorption through gastric retention. We hypothesise that this approach could lead to the reduction of dosing frequency for delamanid and thereby has potential to improve adherence. Formulations of delamanid were prepared in selachyl alcohol and phytantriol as non-digestible self-assembling lipid vehicles, and their behaviour was compared with reconstituted milk powder, as a digestible lipid-based formulation, and an aqueous suspension. The self-assembly of selachyl alcohol and phytantriol in aqueous media in the presence of delamanid was studied using small angle X-ray scattering and produced the inverse hexagonal (H 2 ) and inverse bicontinuous cubic (V 2 ) liquid crystal structures, respectively. The times at which maximum delamanid levels in plasma were observed (T max ) after oral administration of the phytantriol, selachyl alcohol and reconstituted milk powder formulations of delamanid to rats were 27 ± 3, 20 ± 4 and 6.5 ± 1.0 h, respectively, compared with the aqueous suspension formulation with a T max of 3.4 ± 1 h, which confirms the hypothesis of an extended duration of absorption after administration in non-digestible self-assembling lipids. The digestion products of the triglycerides in the milk formulation increased the solubilisation of delamanid in the gastrointestinal tract, leading to an increase in exposure compared with the aqueous suspension formulation but did not significantly extend T max . Overall, the non-digestible nanostructured lipid formulations extended the duration of absorption of delamanid well beyond that from milk or suspension formulations.

Deconstructing compassionate conservation - Matt W. Hayward; Alex Callen; Benjamin L. Allen; Guy Ballard; Femke Broekhuis; Cassandra Bugir; Rohan H. Clarke; John Clulow; Simon Clulow; Jennifer C. Daltry; Harriet T. Davies‐Mostert; Peter J. S. Fleming; et al. (Conservation Biology, 2019)
Compassionate conservation focuses on 4 tenets: first, do no harm; individuals matter; inclusivity of individual animals; and peaceful coexistence between humans and animals. Recently, compassionate conservation has been promoted as an alternative to conventional conservation philosophy. We believe examples presented by compassionate conservationists are deliberately or arbitrarily chosen to focus on mammals; inherently not compassionate; and offer ineffective conservation solutions. Compassionate conservation arbitrarily focuses on charismatic species, notably large predators and megaherbivores. The philosophy is not compassionate when it leaves invasive predators in the environment to cause harm to vastly more individuals of native species or uses the fear of harm by apex predators to terrorize mesopredators. Hindering the control of exotic species (megafauna, predators) in situ will not improve the conservation condition of the majority of biodiversity. The positions taken by so‐called compassionate conservationists on particular species and on conservation actions could be extended to hinder other forms of conservation, including translocations, conservation fencing, and fertility control. Animal welfare is incredibly important to conservation, but ironically compassionate conservation does not offer the best welfare outcomes to animals and is often ineffective in achieving conservation goals. Consequently, compassionate conservation may threaten public and governmental support for conservation because of the limited understanding of conservation problems by the general public.